Reciprocating and Connecting: The Ritual Structure and Social Functions of Yao Huan Jia Yuan in Huangdong, Southwest China - Zhang, Yue (Religions, 2021)
One of the traditional religious rituals of the Yao ethnic group is seeking reciprocal favor for the family from the gods (known as “Huan Jia Yuan”). The cultural value system of the Yao community can be seen in this ritual. Based on fieldwork examining Huan Jia Yuan in Huangdong Township, Hezhou City, Guangxi Zhuang Autonomous Region, this article analyzes the symbolism of the ritual, as well as the behavior and psychology of the Yao people. It provides a detailed account of the structure and process of the ritual and examines the religious function of Huan Jia Yuan. It demonstrates that Huan Jia Yuan is a ritual by which Yao people communicate and exchange with gods through offerings and sacrifices. In return, the gods promise to eliminate disasters and to use their sacred powers to help those who are experiencing difficulties. In modern society, maintaining cultural inheritance and fostering connections between people are very important. As a result, the ritual has changed in response to the changing life of the community.